Using a Proteomic Approach to Differentiate Saccharomyces cerevisiae for Superior Alternative Protein Sources - Zhao, Yan; Chen, Bingyu; Zhang, Xiaoyue; Zhu, Xuchun; Huang, Mingzheng; Liu, Hongzhi (Journal of agricultural and food chemistry, 2025)
This study aims to screen yeast strains with a high protein content from a proteomics perspective, with the aim of exploring potential sustainable sources of alternative protein. A comparative proteomics analysis of four nonindustrial brewing yeasts revealed that proteins involved in synthesis and degradation were significantly more prevalent in high-protein strains. Yeast-A (Y-A) strain, which had the highest protein content (54.26 ± 0.89/100 g) and fastest growth rate, was selected for in-depth functional analysis. Differentially expressed proteins (such as and ) were identified using fold change (FC > 2 or FC < 1/2) and -value ( < 0.01) as thresholds. These findings imply that protein synthesis and degradation pathways coordinate transcription and translation to regulate protein content and growth. Future research should focus on optimizing these pathways through genetic engineering to enhance the efficiency with which yeast produces protein.